2020
DOI: 10.1002/saj2.20085
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and biochemical composition of ground‐dwelling bee nests in agricultural settings

Abstract: Soils deliver under‐recognized ecosystem services by supplying habitat for ground‐dwelling pollinators, such as wild bees and other organisms, that pollinate 80% of insect‐pollinated plants and play a critical role in securing resilient pollination provisions. Our objective is to identify soil properties of ground‐nesting bee nests in agricultural settings of western Oregon. We confirmed ground‐nesting bee and sand wasp activity in seven agricultural sites and one recreational park. Soils from 17 bee and sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“… Antoine and Forrest (2020) observed that Andrenidae species prefer comparatively compact surfaces for construction of their nesting cavity. Generally, among all wild bee species the clay soils are most preferred for nest construction; while as some wasp species prefer soils with higher proportion of sand (90%) ( Lybrand et al2020 ). Normally we observed, females make short round flights around the nest and come back to nest entrance, and it is assumed that low temperature may be responsible for their short flights.…”
Section: Discussionmentioning
confidence: 99%
“… Antoine and Forrest (2020) observed that Andrenidae species prefer comparatively compact surfaces for construction of their nesting cavity. Generally, among all wild bee species the clay soils are most preferred for nest construction; while as some wasp species prefer soils with higher proportion of sand (90%) ( Lybrand et al2020 ). Normally we observed, females make short round flights around the nest and come back to nest entrance, and it is assumed that low temperature may be responsible for their short flights.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared whether our traps were similarly distributed with respect to slope and aspect between treatments using a chi‐square test, as slope and aspect may influence bee preferences for nesting (Lybrand et al, 2020; Potts & Willmer, 1997; R Core Team, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…the vast majority of non-parasitic bees [116,117] and several ant species) and for those that use soil to construct their cells above ground (e.g. Megachillidae [118]), the impacts of altered soil properties can be profound [119].…”
Section: Effects Mediated By Changes On Nesting Resourcesmentioning
confidence: 99%